Primary extrathoracic extraskeletal osteosarcoma of the chest wall: A rare entity - Rahul Bisht; Ajin Anto; Raj Mohan; Surjeet Dwivedi (Wolters Kluwer Medknow Publications, 2023)
Extraskeletal osteosarcoma (ESOS) is a rapidly growing malignant neoplasm-producing osteoid, located in the soft tissues other than bones or periosteum. Primary ESOS presenting in extrathoracic locations is very rare. The optimal treatment of ESOS is largely unknown. The most common location is the soft tissues of the thigh (46%), upper extremity (20%), intrathoracic (rare), and retroperitoneum (17%). These tumors are usually large while diagnosis, typically measures 10 cm in diameter. The diagnosis is by core biopsy and microscopy sections reveal spindle cells with high NC ratio, myxoid stroma, osteoid matrix, and necrosis. Immunohistochemistry reveals that the tumor cells are positive for Desmin (40%), CD99 (25%), NKX2.2 (30%), and myogenin (15%). The radiological differentials include posttraumatic myositis ossificans. The treatment consists of wide surgical resection and reconstruction depends on the defect. Patients with localized disease were treated with an osteosarcoma-type adjuvant chemotherapy regimen consisting of doxorubicin, and cisplatin. The prognosis is poor when compared with intra-osseous osteosarcoma. More than 90% of patients develop local and distant metastasis and recurrence is between 2 months and 10 years. We hereby describe the case of giant ESOS of the chest wall, which was managed successfully at our center. A 58-year-old male presented with rapid progressive malignant ESOS in the right side chest 20 cm × 20 cm. He was managed by a multidisciplinary team of oncosurgery, plastic surgeon, and onco medicine by neoadjuvant chemotherapy and wide local excision with latissimus dorsi pedicle reconstruction. On a 3-year follow-up, he had no recurrence and doing well.